Contraceptive uptake and characteristics in the immediate postpartum period among women attending Tygerberg Academic Hospital - Denise Sproul; Michael McCaul; Gerhard Hanekom (PLoS ONE, 2026)
The immediate postpartum period is a unique opportunity to motivate and educate women on family planning options. This study aimed to determine the prevalence of family planning use in our setting. Secondary objectives include determining the frequency of the various methods used, the safety of the method(s), common risk factors, the interval spacing between births and associations with family planning method choices. A cross-sectional study was conducted at Tygerberg Academic Hospital, South Africa, which serves a predominantly low socioeconomic status and high-risk obstetric population. Medical records were assessed prospectively from January 2023 till July 2023. Data was collected and captured from maternity medical records on the day of discharge. The statistical analysis was done using frequencies and percentages, with 95% confidence intervals (95%CI). A secondary bivariant analysis was done to evaluate the associations between these variables. Of the 1066 participants included, 97.5% (95%CI 96.5–98.5) received family planning. The majority of the patients (48.8%) requested the injectable depo medroxyprogesterone acetate. These patients who chose this method were on average younger (OR 0.962, p < 0.001), had a lower BMI (OR 0.983, p = 0.012), and were a higher parity (OR 0.721, p < 0.001). HIV positive women were also 35% less likely (OR 0.651, p = 0.008) to choose this method compared to other methods. Of the 1039 patients who had received family planning, 47.8% were classified into a World Health Organization medical eligibility category three. This was almost exclusively attributed due to patients who were breastfeeding and requested the depo medroxyprogesterone acetate as their family planning method postpartum. The majority (66%) of the patients had spaced their pregnancies more than two years apart. The exceptionally high prevalence of uptake of family planning indicates it can be successfully implemented in the postpartum period. Patients should be counselled individually on the safest and the most appropriate method.